Do Boys Empathize Less than Girls? Exploring the Links Among Empathy, Gender and Sexist Attitudes in Adolescents - Magaly Luisina García-Senlle; Manuel Martín-Fernández; Raquel Conchell; Sara Arrojo; Marisol Lila (Behavioral Sciences)
(1) Background: Intimate partner violence (IPV) remains a pervasive issue, particularly among adolescents. Its prevalence is still high despite intervention efforts, especially for younger generations. Empathy and sexism are factors linked with IPV that have shown gender differences. This study focuses on how gender moderates the association of empathy and sexist attitudes among adolescents in Spain; (2) Methods: A two-stage stratified cluster sampling method for collecting data from 516 adolescents (219 boys, 297 girls) aged 12–18 years was used. Participants completed the Ambivalent Sexism Inventory and the Interpersonal Reactivity Index. Hierarchical multiple regression analyzed the moderating role of gender in the relation between empathy and ambivalent sexism; (3) Results: Boys exhibited higher sexism levels than girls. Perspective taking negatively predicted hostile sexism. Empathic concern positively predicted hostile and benevolent sexism. Significant gender-specific patterns emerged: more empathic concern was linked with increased hostile sexism in boys; higher perspective taking was linked with increased benevolent sexism in boys, but was lower in girls; (4) Conclusions: There is a complex interplay among empathy, gender, and sexism, suggesting that IPV prevention programs should be tailored differently for boys and girls by considering broader socio-political contexts, addressing traditional gender norms, and promoting gender equality.